1999
DOI: 10.1111/j.1439-0426.1999.tb00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of osmotic and ionic regulation in Adriatic sturgeon Acipenser naccarii. II: Morpho-physiological adjustments to hyperosmotic environments

Abstract: A salt water exposure trial with juvenile Adriatic sturgeon, Acipenser naccarii, ( 5 months old; mean (* SD) weight = 56f28 g) was initiated by direct transfer from freshwater (FW) to brackish water (BW) of medium (310 mOsm.Kg-' = 11 %) or high salinity (640 mOsm.Kg-' = 23 960). Survival at 6 weeks and homeostatic regulation of plasma osmolality and ion concentrations demonstrated that A. naccarii of this age and/or size class possess the ability to adapt to hyperosmotic environments. Regulation of the osmotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 23 publications
9
43
2
Order By: Relevance
“…In some other studies also, the gill NKA activity followed this pattern, as the lowest NKA activity levels were obtained in brackishwater conditions (Laiz-Carrion et al, 2005;Kang et al, 2008;Kang et al, 2012;Khodabandeh et al, 2009a). Since NKA is highly expressed in fish gill ionocytes, its activity at the gill level is expected to be reduced with decreased ionocyte size and number (Evans, 1993;Cataldi et al, 1995;McCormick, 1996;McKenzie et al, 1999;Mancera and McCormick, 2000). Low values of the ionocyte size, number and the gill NKA activity reported previously in the literature for fish acclimated to brackishwater has been confirmed in the current study, especially for 1g fingerlings, by a reduction in the number and size of ionocytes under similar conditions.…”
Section: Resultssupporting
confidence: 86%
“…In some other studies also, the gill NKA activity followed this pattern, as the lowest NKA activity levels were obtained in brackishwater conditions (Laiz-Carrion et al, 2005;Kang et al, 2008;Kang et al, 2012;Khodabandeh et al, 2009a). Since NKA is highly expressed in fish gill ionocytes, its activity at the gill level is expected to be reduced with decreased ionocyte size and number (Evans, 1993;Cataldi et al, 1995;McCormick, 1996;McKenzie et al, 1999;Mancera and McCormick, 2000). Low values of the ionocyte size, number and the gill NKA activity reported previously in the literature for fish acclimated to brackishwater has been confirmed in the current study, especially for 1g fingerlings, by a reduction in the number and size of ionocytes under similar conditions.…”
Section: Resultssupporting
confidence: 86%
“…naccarii, Cataldi et al 1995bA. naccarii, Cataldi et al , 1999McKenzie et al 1999;Martínez-Á lvarez et al 2002). These changes can be attributed to changes in the water content in the blood, caused by the change in environmental salinity (Plaut 1998).…”
Section: Discussionmentioning
confidence: 94%
“…Juveniles have higher osmolality and plasma ion levels than adults of the same species in the same salinities Cech 1985, 1987 ; Table 4). Presumably, because sturgeons hatch and grow at least initially in FW, they regulate at elevated ion homeostasis levels in hyperosmotic salinities, as compared to hyposmotic salinities Cech 1985, 1987;Altinok et al 1998;Krayushkina 1998;McKenzie et al 1999;Rodriguez et al 2002). Some juveniles also appear to regulate at nearly isosmotic levels, when salinities are approximately 8-12& (Natochin et al 1985;Shelukhin et al 1990).…”
Section: Osmoregulationmentioning
confidence: 92%
“…Most recent studies on the aerobic metabolic costs of salinity in teleosts have not found large costs (Boeuf and Payan 2001), except when salinities are changing rapidly (Morgan et al 1997). Although some aerobic metabolic studies have been conducted on sturgeon juveniles at different salinities (Shelukhin et al 1990;Secor and Gunderson 1998;McKenzie et al 1999McKenzie et al , 2001a, there have been no studies investigating size or age effects on salinity-associated metabolic costs. Metabolism measurements, as physiological tools, can be used to make predictions about organisms' optimal environmental conditions (Cech 1990).…”
Section: Introductionmentioning
confidence: 96%